Improved Chloride Ion Sensing Performance of Flexible Ag-NPs/AgCl Electrode Sensor Using Cu-BTC as an Effective Adsorption Layer - Kwak, Byungkwan; Park, Soobin; Lee, Han-Seung; Kim, Jiwon; Yoo, Bongyoung (Frontiers in Chemistry, 2019)
We designed a flexible chloride ion selective sensor that directly monitors electrochemical reactions of chloride ions without using a reference electrode. A flexible polytetrafluoroethylene (PTFE) substrate was utilized to provide bendability to the fabricated sensor. As an ion selective material, Ag nanoparticles (NPs) were employed on the multi-walled carbon nanotubes (MWCNTs) loaded on the PTFE substrate. Enhanced adsorption property of the fabricated sensor toward chloride ions was achieved by incorporating hydrophilic copper benzene-1,3,5-tricarboxylate (Cu-BTC), which has significant flexibility and stability. Accordingly, compared with the bare sensor, the sensing performance of the Cu-BTC-treated Ag NPs/AgCl electrode sensor was improved as indicated by an approximately four times reduction in the response and recovery times. This indicated that the Cu-BTC layer could function as an effective medium between the surface of Ag NPs and the electrolyte containing chloride ions. It is observed from contact angle measurement that the hydrophilicity significantly increased in the Cu-BTC-treated sensor because the exposed surface of the sensor not treated by Cu-BTC largely consisted of hydrophobic MWCNTs. Furthermore, the Cu-BTC layer could hold the electrolyte for effective adsorption of analytes with a large specific surface area.